Body composition of patients on a very low-protein diet: a two-year survey with DEXA - Chauveau, Philippe; Vendrely, Benot; El Haggan, Wael; Barthe, Nicole; Rigalleau, Vincent; Combe, Christian; Aparicio, Michel (Journal of renal nutrition, 2003)
It has been reported that patients on a very-low-protein diet (VLPD) maintain a satisfactory nutritional status because of a conserved adaptive metabolic response. However, only few studies have examined the course of nutritional status and body composition in the long term (2 years). Thirteen stable patients (8 men; age, 55 +/- 12 years; glomerular filtration rate (GFR), 15 +/- 5 mL/min) receiving a VLPD (0.3 g/kg/day protein) supplemented with amino acids and ketoanalogues (SVLPD) were studied for 2 years. A joint visit with a physician and a dietitian and routine blood and urine analyses were performed every month. Dual-energy x-ray absorptiometry (DEXA), which was used to assess modification of body composition, and GFR (urinary 51Cr-EDTA) and urinary urea and creatinine excretion, which were used to assess nutritional status and compliance to the diet, were assessed every 3 months. GFR, albumin, and prealbumin levels remained stable. Urea urinary excretion decreased at 3 months and then slightly increased at 2 years, but the calculated protein intake remained low at 0.38 +/- 0.1 g/kg/day. Energy intake remained close to 30 kcal/kg/day. No significant change was observed for total fat mass or percent fat mass. After an initial decrease, lean body mass stabilized at 6 months and then increased significantly from 6 to 24 months (P =.02, paired t-test); the mean increase during this period was of 2 kg, that is, 4.6%. Urinary creatinine excretion showed the same profile. Total bone mass, lumbar or hip site bone mass, and Z-score significantly decreased from T0 to 1 and 2 years (P <.05). This study confirms that a supplemented VLPD is nutritionally safe for a long period, but attention must be paid to bone mass.